Religious Moderation and Social Fiqh: Reconstructing Islamic Legal Responses to Cultural Diversity in Indonesia - Mutiara Azizah; Hidayat Azhar Al Ikhlash; Muhammad Akbar (Faculty Sharia of State Islamic University (UIN) Palangka Raya, 2025)
Indonesia, as a pluralistic nation with remarkable religious, cultural, and ethnic diversity, faces both opportunities and challenges in maintaining social cohesion. Religious moderation has emerged as a strategic approach to balance religious devotion with respect for cultural plurality. From the perspective of social jurisprudence (fiqh sosial), religious moderation transcends its theological dimensions to function as a social instrument for fostering harmony, justice, and public order. This article examines the significance of religious moderation in navigating cultural differences and its relevance to social law in Indonesia. Employing a library research method with a descriptive-analytical approach, this study analyzes primary and secondary sources on Islamic jurisprudence, social law, and religious moderation policies in Indonesia. The findings reveal that religious moderation functions as a social control mechanism that acknowledges cultural plurality while maintaining Islamic legal principles. The integration of moderation values into social fiqh provides a framework for resolving cultural tensions, accommodating local traditions, and strengthening national resilience. This research contributes to the growing discourse on Islamic legal reconstruction in multicultural societies and offers practical implications for policymakers, religious leaders, and educators in promoting inclusive religious practices within Indonesia's diverse socio-legal landscape.